ANALISIS FAKTOR-FAKTOR PENGHAMBAT MEMBACA PERMULAAN PADA SISWA DI FASE A SD - Ridho, Muhammad; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
Early reading learning is a very important early stage in elementary education, but many students still have difficulty reading due to various factors. The results of a study at Tegalmulyo State Elementary School showed that the less varied learning methods and minimal use of interactive media caused students to feel bored and less enthusiastic in learning to read. The lack of interesting reading materials and learning models that were not in accordance with students' learning styles also contributed to their low understanding of reading texts. In addition, parental involvement in supporting children's reading habits at home still varies, where some students do not get enough guidance. Therefore, more innovative learning methods are needed, such as story-based approaches, educational games, and the use of technology so that students are more interested in reading. With cooperation between teachers, schools, and parents, it is hoped that students can improve their reading skills optimally and enjoy the learning process more enjoyable